Kelayakan Limbah Sisik Ikan Nila Menjadi Produk Kreatif Aksesoris Nail Art - Salsa Alya Mafaza; Ifa Nurhayati; Godham Eko Saputro (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the feasibility of tilapia scale waste as a basic material for making nail art accessories that have economic and environmentally friendly value. The research was carried out at Nail's By Valeta, Pakintelan, Gunung Pati District, Semarang City using a quantitative descriptive approach through the experimental one-shot case study method. The test was carried out through two stages, namely the product validity test by three expert judgments and the preference test by 30 trained respondents. The results of the validity test showed that nail art accessories products obtained an average score of 94.3% with the category